The Affective Assessment Crisis: Deconstructing the Failure of Internalizing Islamic Ecotheology within the Merdeka Curriculum in PAI - Herawati, Susi; Ramli, Syahrur; Trisoni, Ridwal; Thongin, Arthit; Maimori, Romi; Sesmiarni, Zulfani; Akbar, M Ravi (Berkala Ilmiah Pendidikan, 2026)
This study investigates the "internalization deficit" in Islamic ecotheology at MAN 1 Tanah Datar, where the flexibility of the Merdeka Curriculum paradoxically leads to the neglect of affective dimensions. The research aims to bridge the cognitive-affective gap by leveraging a meaningful learning framework to address superficial environmental ethics. The primary focus is directed toward deconstructing current assessment models that fail to engage the spiritual and emotional dimensions of students in Islamic Education (PAI). Utilizing a qualitative phenomenological design, data were collected through in-depth interviews, participant observation, and data triangulation involving 5 PAI teachers and 15 students. The results reveal a profound "affective void," as curriculum implementation prioritizes cognitive mastery and administrative reporting over spiritual cultivation. Current evaluation instruments are hindered by a "quantification bias" that measures only administrative compliance, preventing ecotheological values from internalizing into authentic behavioral traits (akhlak). The study concludes that internalizing ecological values requires the adoption of "slow pedagogy" and a transition toward qualitative-affective assessment methods, such as reflective journals and long-term behavioral tracking in local ecosystems. These findings recommend a reconstruction of authentic environmental ethics by prioritizing sincerity (ikhlas) and spiritual responsibility as stewards of the Earth (Khalifah).